PENGABDIAN MASYARAKAT PENGETAHUAN IBU TENTANG MOTORIK KASAR PADA ANAK USIA 3-5 TAHUN DI DESA TUMPUK KECAMATAN SAWOO KABUPATEN PONOROGO - Wibowo, Dodik; Muchsin, Enur Nurhayati; Tanoto, Wahyu (STIKES dan AKZI Karya Husada Kediri, 2024)
Gross motor skills are physical skills that involve the muscles of the body from the fingertips as well as eye and hand coordination. Mothers' knowledge about gross motor skills can be drilled and developed through routine activities and stimulation such as training children to play on bicycles and go up and down stairs. This community service activity is aimed at increasing mothers' knowledge about gross motor skills in children aged 3-5 years in Tumpuk Village, Sawoo District, Ponorogo Regency. The population in this activity were all mothers who had children aged 3-5 years, a total of 250 people. Through purposive sampling techniques, 50 respondents were obtained as samples. Research variable data on maternal knowledge about gross motor skills were taken using a questionnaire. Data analysis uses a percentage formula and the results are presented quantitatively. The results of the activity showed that the majority of mothers' knowledge about gross motor skills from 50 respondents, namely 41 respondents (82%) had good knowledge about gross motor skills in children aged 3-5 years, then 5 respondents (10%) had sufficient knowledge. And 4 respondents (8%) had insufficient knowledge about gross motor skills in children aged 3-5 years. The mother's knowledge about gross motor skills is influenced by several factors, namely previous education, employment, income, number of children, how many children, ever received information, and source of information. It is recommended that respondents always increase their knowledge of gross motor skills in children aged 3-5 years so that children's growth and development can be maximized.